A Co-Expression Network Reveals the Potential Regulatory Mechanism of lncRNAs in Relapsed Hepatocellular Carcinoma - Fang, Yuan; Yang, Yang; Zhang, XiaoLi; Li, Na; Yuan, Bo; Jin, Li; Bao, Sheng; Li, MengGe; Zhao, Dan; Li, LingRui; Zeng, Zhong; Huang, HanFei (Frontiers in Oncology, 2021)
Background: The mechanistic basis for the relapse of hepatocellular carcinoma (HCC) remains poorly understood. Recent research has highlighted the important roles of long non-coding RNAs (lncRNAs) in HCC. However, there are only a few studies on lncRNAs associated with the relapse of HCC. Methods: We analyzed lncRNA and mRNA profiles in the GSE101432 dataset associated with HCC relapse. The differentially expressed lncRNAs and mRNAs were used to construct a lncRNA-mRNA co-expression network. Weighted gene co-expression network analysis followed by Gene Ontology and Kyoto Encyclopedia of Genes and Genomes enrichment analyses were conducted on the database. Furthermore, correlation and survival analyses were performed using The Cancer Genome Atlas database, and the clinical samples were verified by qRT-PCR. Results: In this study, lncRNAs and mRNAs associated with HCC relapse were identified. Two gene modules were found to be closely linked to HCC relapse. The functional enrichment analysis results of lncRNAs and co-expression mRNAs indicated that they were closely related to the relapse of HCC. In addition, we verified that the overall survival and recurrence-free survival of these genes in HCC have survival prediction functions. In total, we identified and validated two lncRNAs (LINC00941 and LINC00668) and six mRNAs (LOX, MICB, OTX1, BAIAP2L2, KCTD17, NDUFA4L2) associated with HCC relapse. Conclusion: In summary, we identified the key gene modules and central genes associated with relapse of HCC, and constructed lncRNA-mRNA networks related to this cancer type. These results provide a foundation for future basic research on the mechanism of relapse of HCC.